Automatic Door Lock Design with Arduino Mega 2560 Based Knocking Rhythm - Atmiasri; Melkior Baltasar Kasper Poso (BEST, 2023)
As the development of knowledge and technology in the world of education is currently advancing rapidly, many provide ideas for new methods and innovations in the field of technological development, especially automatic door locks with a rhythm of knocking. Door locks are vulnerable to the risk of being left behind or lost, protection or security is needed to store them. This research is designed to build a private room door security by using the knock pattern of the process by performing a knock, identification to verification of each recognized knock pattern. The system will start working by doing the accuracy of the interval between knocks when the rhythm / rhythm of knocking based on previously stored data then the system is active, from that developed a tool that is used as a room door lock by knocking on the door with a rhythm / rhythm that has been adjusted to the knock. Using this tool is expected to help and maintain better room security.